Development and application of an LC-MS method to the determination of poly- and perfluoroalkyl substances (PFASs) in drinking, sea and surface water samples - Huerta, Belinda; McHugh, Brendan; Regan, Fiona (Analytical Methods, 2022)
Poly- and perfluoroalkyl substances (PFASs) are a group of synthetic organic surfactants that have become a global concern because of their toxicity and widespread presence in the aquatic environment and organisms globally. In this study, a new analytical method has been developed and validated for the analysis of 15 perfluorinated compounds in different water matrices: river water, drinking water and seawater. Water extraction was performed in anion exchange solid phase extraction cartridges, and extracts were analysed by liquid chromatography in tandem with mass spectrometry. Recoveries for target analytes were between 35 and 120%, depending on the water matrix. Method detection limits were in the range of 0.5–17 ng L−1. The validated method was applied to the determination of perfluorinated compounds in water samples around Ireland. Eight compounds out of fifteen were detected at least in one sample. Measured concentrations were higher in river water than seawater, and drinking water had the lowest levels, although still detectable for a considerable amount of compounds. The most prevalent compounds were PFPeA, PFOA and PFHxA, present in all types of water, and they had the highest concentrations.
Keywords: dept.che; peer-reviewed

Interaction of egg cortisol and offspring experience influences stress-related behaviour and physiology in lake sturgeon - Wassink, Lydia; Huerta, Belinda; Li, Weiming; Scribner, Kim (Animal Behaviour, 2020)
Quantifying transgenerational effects of stress is important to predict outcomes of anthropogenic disturbances for wildlife species. Maternal stress can programme physiological and behavioural phenotypes in offspring, which may be maladaptive if maternal and offspring environments are mismatched. We investigated effects of a match and mismatch between egg cortisol and offspring stress levels in lake sturgeon, Acipenser fulvescens, using artificially elevated egg cortisol levels (simulating maternal stress) and a chronic unpredictable stress regime for offspring after hatch. Offspring cortisol levels were quantified at baseline and after an acute stressor. Multiple measures of offspring swimming activity were assessed in behaviour trials. Individuals that experienced elevated egg cortisol and high offspring stress exhibited a diminished cortisol response to an acute stressor, but responses varied among offspring from different families. Results suggest that the interaction between maternal and offspring experience may cue an offspring phenotype that is adaptive in high-stress conditions. Principal components analysis characterizing interindividual variation in offspring behavioural variables showed that treatment significantly affected multivariate offspring response along the PC1 axis (associated with inactivity), and both treatment and family significantly affected response along the PC2 axis (associated with shorter distance moved). The largest differences for PC1 occurred between the ‘mismatch’ treatments (high egg cortisol and low offspring stress exhibiting lower activity; low egg cortisol and high offspring stress exhibiting higher activity), indicating that the combination of egg cortisol and offspring stress is more important in determining offspring behaviour than is egg cortisol or offspring stress alone. Findings suggest that family effects, such as genetic components or maternal experience, may mediate how the interaction of maternal and offspring stress influences offspring physiological and behavioural outcomes, and indicate the need for further research into environmental factors experienced by females that influence how offspring respond to egg cortisol and early life stress.
Keywords: behaviour; cortisol; dept.che; eggs; lake sturgeon; maternal stress; peer-reviewed; physiology

Liver metabolomic profiles of sea lamprey (Petromyzon marinus) are influenced by sex and maturation stages - Tamrakar, Sonam; Huerta, Belinda; Chung‐Davidson, Yu‐Wen; Li, Weiming (Metabolomics, 2025)
INTRODUCTION: Sea lamprey (Petromyzon marinus) is a unique vertebrate model to examine how liver metabolomes support different reproductive functions. Juvenile sea lamprey prey on other fish species by attaching to their body and feeding on their blood and body fluids. Once reaching adulthood, they cease feeding, migrate to spawning streams and begin their final sexual maturation. During these processes, the male livers produce large quantities of bile acid pheromone precursors to be modified and released via gills, whereas the female livers synthesize vast amounts of vitellogenin (yolk lipophosphoprotein) to be transported to the ovary. OBJECTIVE: We aim to test the hypothesis that the liver metabolic pathways exhibit dramatic changes during sexual maturation of sea lampreys that support their reproductive strategies. METHODS: Liver tissues from prespermiating (PSM) and spermiating (SM) males, and preovulatory (POF) and ovulatory (OF) females were homogenized, extracted and analyzed using the Thermo Q-exactive Orbitrap UPLC/MS/MS. Progenesis QI, Compound Discoverer, and Metaboanalyst were used for alignment, peak picking, deconvolution, and annotation. Data were subjected to analyses such as PCA and PLS-DA, using the SIMCA® software. The glycogen and triglyceride content in liver were also examined to determine levels of stored energy. RESULTS: Overall, we found upregulations of amino acid and fatty acid metabolisms in mature male sea lamprey compared to the immature ones. Although the metabolic differences were comparatively subdued in the sexually immature males and females, amino acid regulation was slightly higher in females. CONCLUSION: We conclude that the metabolic dynamics in sea lamprey livers are consistent with their reproductive strategies.
Keywords: Bile acids; Bioinformatics; Biology; Computational biology; Fatty acids; Fishery; Hepatic Physiology; Hepatocytes; Hepatology; Lamprey; Maturation; Metabolism; Metabolomics; Petromyzon; Petromyzon marinus; Reproductive Physiology; Sex; Untargeted metabolomics; Zoology; dept.che; peer-reviewed

Plasma metabolomic profiles reveal sex- and maturation-dependent metabolic strategies in sea lamprey (Petromyzon marinus) - Tamrakar, Sonam; Huerta, Belinda; Chung-Davidson, Yu-Wen; Li, Weiming (Metabolomics: Official Journal of the Metabolomic Society, 2022)
INTRODUCTION: Adult sea lamprey (Petromyzon marinus) cease feeding and migrate to spawning streams where males build nests, undergo final sexual maturation, and subsequently produce and release large quantities of bile acid pheromones that attract mature females. These animals are predicted to rearrange their metabolic pathways drastically to support their reproductive strategies, presenting advantageous opportunities to examine how sex and the maturation processes affect metabolism. OBJECTIVES: The objective is to investigate the metabolic differences between sexes and maturation states in sea lamprey that support changes in physiological functions. METHODS: We compared plasma metabolomes of spawning and prespawning sea lamprey in both sexes using both non-targeted and targeted metabolomics approaches using UPLC/MS-MS with electrospray ionization in both positive and negative modes. The data were processed using Progenesis QI, Compound Discoverer and XCMS softwares for alignment, peak picking, and deconvolution of the peaks. Principle component analyses (PCA) and partial least squares discriminant analyses (PLS-DA) were performed using SIMCA and Metaboanalyst softwares to identify discriminating features, followed by fragmentation matching with extensive database search and pathway mapping. RESULTS: The pheromonal bile acid biosynthesis was upregulated significantly in males compared to females. Spermiating males further upregulated bile acid biosynthesis by altering amino acid metabolisms, upregulating cofactors and nucleotide metabolisms, but downregulating carbohydrate and energy metabolisms. CONCLUSION: Plasma metabolomes are sex- and maturation-dependent and reflect the special metabolic demands at each life stage and reproductive strategy.
2 citations (Crossref) [2023-10-31]
Keywords: Animals; Bile Acids and Salts; Bile acid biosynthesis; Female; Male; Metabolic pathways; Metabolomics; Petromyzon; Petromyzon marinus; Sexual Maturation; Sexual selection; Tandem Mass Spectrometry; Targeted analyses; Untargeted analyses; dept.che; peer-reviewed

Hatchery and wild larval lake sturgeon experience effects of captivity on stress reactivity, behavior and predation risk - Wassink, Lydia; Huerta, Belinda; Larson, Doug; Li, Weiming; Scribner, Kim (Conservation Physiology, 2022)
Reintroduction programs are important tools for wildlife conservation. However, captive rearing environments may lead to maladaptive behavior and physiological alterations that reduce survival probability after release. For captive rearing programs that raise individuals captured from the wild during early ontogeny for later release, there is a lack of information about when during ontogeny the detrimental effects of captive rearing may become evident. In this study we compared cortisol levels, predation rates and swimming behavior between hatchery-produced and wild-caught larval lake sturgeon (Acipenser fulvescens), a threatened fish species, at three times over 9 days. Cortisol levels did not indicate that hatchery-produced individuals were more stressed, but cortisol reactivity to an acute stressor disappeared for both hatchery-produced and wild-caught larvae after 9 days in the hatchery. Swimming activity levels decreased over time for hatchery-produced larvae but increased over time for wild-caught larvae, suggesting that behavioral trajectories may be programmed prior to the larval stage. Neither increasing nor decreasing activity levels was advantageous for survival, as predation rates increased over time in captivity for larvae from both treatments. Results suggest that physiological and behavioral phenotypes may not accurately predict survival for individuals released from reintroduction programs and that the captive environment may inhibit transition to the wild even if cortisol levels do not indicate high stress. Findings emphasize that even a short amount of time in captivity during early ontogeny can affect phenotypes of individuals captured from wild populations, which may impact the success of reintroduction programs.
Keywords: dept.che; peer-reviewed

Evidence that male sea lamprey increase pheromone release after perceiving a competitor - Fissette, Skye D.; Bussy, Ugo; Huerta, Belinda; Buchinger, Tyler J.; Li, Weiming (Journal of Experimental Biology, 2020)
Sexual signals evolve via selective pressures arising from male–male competition and female choice, including those originating from unintended receivers that detect the signal. For example, males can acquire information from other males signaling to females and alter their own signal. Relative to visual and acoustic signals, less is known about how such communication networks influence chemical signaling among animals. In sea lamprey (Petromyzon marinus), the chemical communication system is essential for reproduction, offering a useful system to study a pheromone communication network that includes signalers and both intended and unintended receivers. Male sea lamprey aggregate on spawning grounds, where individuals build nests and signal to females using sex pheromones. We examined how exposure to a major component of the male pheromone, 3keto-petromyzonol sulfate (3kPZS), influenced male pheromone signaling, and whether females had a preference for males that altered their signal. Exposure to 3kPZS, at a concentration of 5×10−10 mol l−1, simulated the presence of other male(s) and led to increased 3kPZS release rates within 10 min, followed by a return to baseline levels within 30 min. Exposure also led to increases in hepatic synthesis and circulatory transport of pheromone components. In behavioral assays, females preferred the odor of males that had been exposed to 3kPZS; therefore, males likely benefit from upregulating 3kPZS release after detecting competition for mates. Here, we define how a specific pheromone component influences chemical signaling during intrasexual competition, and show a rare example of how changes in chemical signaling strategies resulting from male competition may influence mate choice.
Keywords: dept.che; peer-reviewed

Waterborne pheromones modulate gonadotropin-inhibitory hormone levels in sea lamprey (Petromyzon marinus) - Chung-Davidson, Yu-Wen; Bussy, Ugo; Fissette, Skye Daniel; Huerta, Belinda; Li, Weiming (General and Comparative Endocrinology, 2020)
The relationships between pheromone stimuli and neuropeptides are not well established in vertebrates due to the limited number of unequivocally identified pheromone molecules. The sea lamprey (Petromyzon marinus) is an advantageous vertebrate model to study the effects of pheromone exposure on neuropeptides since many pheromone molecules and neuropeptides have been identified in this species. Sexually mature male sea lamprey release pheromones 7α, 12α, 24-trihydroxy-5α-cholan-3-one 24-sulfate (3 keto-petromyzonol sulfate, 3kPZS) and 7α, 12α-dihydroxy-5α-cholan-3-one-24-oic acid (3-keto allocholic acid, 3kACA) that differentially regulate gonadotropin-releasing hormone (lGnRH) and steroid levels in sexually immature sea lamprey. However, the effects of these pheromones on gonadotropin-inhibitory hormones (GnIHs), hypothalamic neuropeptides that regulate lGnRH release, are still elusive. In this report, we sought to examine the effects of waterborne pheromones on lamprey GnIH-related neuropeptide levels in sexually immature sea lamprey. Ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) analyses revealed sex differences in GnIH-related neuropeptide levels in the brain and plasma of immature sea lamprey. Exposure to 3kPZS and 3kACA exerted differential effects on GnIH-related neuropeptide levels in both sexes, but the effects were more prominent in female brains. We conclude that sea lamprey pheromones regulate GnIH-related neuropeptide levels in a sexually dimorphic manner.
Keywords: Agnathan; GnIH; NPFF; Primer pheromone; Sex difference; dept.che; peer-reviewed

At the intersection between toxicology and physiology: What we have learned about sea lampreys and bony fish physiology from studying the mode of action of lampricides - Birceanu, Oana; Tessier, Laura R.; Huerta, Belinda; Li, Weiming; McDonald, Allison; Wilkie, Michael P. (Journal of Great Lakes Research, 2021)
The lampricides 3-trifluoromethyl-4-nitrophemol (TFM) and niclosamide have been used for over 60 years to control the invasive sea lamprey (Petromyzon marinus) population in the Laurentian Great Lakes. In this review, we summarize these findings in the context of the mode of action of both lampricides, with a focus on: (1) the physiology of uptake, bodily distribution and mode of action, detoxification, and excretion of lampricides in lamprey and non-target fishes, (2) the development of an Adverse Outcome Pathway for TFM and niclosamide, and (3) the identification of novel avenues for future research that can be further explored to ensure continuous suppression of the sea lamprey population in the Great Lakes. We explored how research on the mode of action of lampricides has provided novel insights into the gill microenvironment and how this impacts lampricide toxicity; described new information on mitochondria and tissue physiology; and discussed how the activity of enzymes that are involved in detoxification pathways impacts the response of fishes to xenobiotics. Considering the information that has been generated over the years on sea lamprey and bony fish physiology from studying the mode of action of lampricides, here we propose an Adverse Outcome Pathway for TFM and niclosamide and identify novel avenues for research on the short and long-term effects of lampricide applications, either alone or in combination. Lastly, we discuss how the differences in physiology between sea lampreys and non-target fishes can be further exploited to ensure continuous suppression of the sea lamprey population in the Great Lakes.
Keywords: Invasive species; Lampricides; Niclosamide; Physiology; TFM; dept.che; peer-reviewed

Abundance of antibiotic resistance genes and bacterial community composition in wild freshwater fish species - Marti, Elisabet; Huerta, Belinda; Rodríguez-Mozaz, Sara; Barceló, Damià; Marcé, Rafael; Balcázar, Jose Luis (Chemosphere, 2018)
This study was aimed to determine the abundance of four antibiotic resistance genes (blaTEM, ermB, qnrS and sulI), as well as bacterial community composition associated with the intestinal mucus of wild freshwater fish species collected from the Foix and La Llosa del Cavall reservoirs, which represent ecosystems with high and low anthropogenic disturbance, respectively. Water and sediments from these reservoirs were also collected and analyzed to determine the pollution level by antibiotics. The blaTEM gene was only detected in brown trout and Ebro barbel, which were collected from La Llosa del Cavall reservoir. In contrast, the sulI and qnrS genes were only detected in common carp, which were collected from the Foix reservoir. Although the ermB gene was also detected in common carp, the values were below the limit of quantification. Likewise, water and sediment samples from the Foix reservoir had higher concentrations and more classes of antibiotics than those from La Llosa del Cavall. Pyrosequencing analysis of 16S rRNA genes revealed significant differences in bacterial communities associated with the intestinal mucus of fish species. Therefore, these findings suggest that anthropogenic activities are not only increasing the pollution of aquatic environments, but also contributing to the emergence and spread of antibiotic resistance in organisms that inhabit such environments.
Keywords: Antibiotic resistance genes; Aquatic environments; Bacterial community composition; Wild fishes; dept.che

Effects of subinhibitory ciprofloxacin concentrations on the abundance of qnrS and composition of bacterial communities from water supply reservoirs - Marti, Elisabet; Huerta, Belinda; Rodríguez-Mozaz, Sara; Barceló, Damià; Balcázar, Jose Luis; Marcé, Rafael (Chemosphere, 2016)
We used a short-term microcosm approach to investigate the influence of two different subinhibitory concentrations of ciprofloxacin (0.01 and 0.1 μg/ml) on both the abundance of a plasmid-mediated quinolone resistance determinant (qnrS) and the structure and composition of bacterial communities from impaired and pristine water supply reservoirs. The results showed that the abundance of the qnrS gene increases in water samples exposed to both subinhibitory concentrations of ciprofloxacin, especially in water samples from La Llosa del Cavall, which represents the pristine system. Subinhibitory ciprofloxacin concentrations also induced changes in bacterial community composition as indicated by the relative abundances of each operational taxonomic unit (OTU) across treatments. Therefore, our findings may be of significant importance because subinhibitory ciprofloxacin concentrations may promote antibiotic resistance and affect bacterial community composition in environmental settings.
Keywords: Antibiotic resistance genes; Aquatic systems; Bacterial community; Quinolones; Water supply reservoirs; dept.che

Sea lamprey cardiac mitochondrial bioenergetics after exposure to TFM and its metabolites - Huerta, Belinda; Chung-Davidson, Yu-Wen; Bussy, Ugo; Zhang, Yizhu; Bazil, Jason N.; Li, Weiming (Aquatic Toxicology, 2020)
Population control of invasive sea lamprey relies heavily on lampricide treatment of infested streams. The lampricide 3-trifluoromethyl-4-nitrophenol (TFM) is thought to impair mitochondrial ATP production through uncoupling oxidative phosphorylation. However, the effect of TFM on the entire electron transport chain (complexes I to V) in the mitochondria is not clear. In addition, TFM is reduced in phase I metabolism by sea lamprey at higher levels than in other fish species. The effects of these TFM reductive metabolites on mitochondria have not been explored. In this study, we sought to examine the effects of TFM and its reductive metabolite amino-TFM (TFMa) on cardiac mitochondrial oxygen consumption and membrane potential to delineate potential mechanisms for toxicity. To determine if molecules with similar structure also exhibit similar effects on mitochondria, we used 4-nitro-3-methylphenol (NMP) and its reductive metabolites 4-amino-3-methylphenol (NMPa) and 4-nitroso-3-methylphenol (NMPn) for comparisons. We found that mitochondrial bioenergetics was heavily affected with increasing concentrations of TFM, NMP, and NMPa when complexes I and II of the electron transport chain were examined, indicating that the toxic action of these compounds was exerted not only by uncoupling complex V, but also affecting complexes I and II.
Keywords: Lampricides; Mitochondria toxicity; Reductive metabolism; Sea lamprey; dept.che; peer-reviewed

Presence of pharmaceuticals in fish collected from urban rivers in the U.S. EPA 2008–2009 National Rivers and Streams Assessment - Huerta, Belinda; Rodriguez-Mozaz, Sara; Lazorchak, Jim; Barcelo, Damia; Batt, Angela; Wathen, John; Stahl, Leanne (Science of The Total Environment, 2018)
Fish are good indicators of aquatic environment pollution because of their capability to uptake pollutants contained in water. Therefore, accumulation of pharmaceutical compounds in freshwater and marine fish and other aquatic organisms has been studied extensively in the last decade. In this context, the present study investigates the occurrence of pharmaceutical compounds in wild fish from 25 polluted river sites in the USA, downstream from wastewater treatment plants (WWTPs). Sample sites constitute a subset of urban rivers investigated in the U.S. EPA's 2008–2009 National Rivers and Streams Assessment. Thirteen pharmaceuticals (out of the twenty compounds analyzed) were quantified in fish fillets at concentrations commonly below 10ngg−1, in accordance with the findings from previous studies in the USA and Europe. The psychoactive drugs venlafaxine, carbamazepine and its metabolite 2-hydroxy carbamazepine were the most prevalent compounds (58%, 27% and 42%, respectively). This group of drugs is highly prescribed and rather resistant to degradation during conventional treatment in WWTPs as well as in natural aquatic environments. Salbutamol, a drug used to treat asthma, and the diuretic hydrochlorothiazide were also frequently detected (in >20% of the samples). Occurrence of six pharmaceutical families due to chronic exposure at environmental concentrations in water was detected in eight fish species.
Keywords: Accumulation; Fish; Pharmaceuticals; Trophic level; dept.che

Bioaccumulation and trophic magnification of pharmaceuticals and endocrine disruptors in a Mediterranean river food web - Ruhí, Albert; Acuña, Vicenç; Barceló, Damià; Huerta, Belinda; Mor, Jordi-Rene; Rodríguez-Mozaz, Sara; Sabater, Sergi (Science of The Total Environment, 2016)
Increasing evidence exists that emerging pollutants such as pharmaceuticals (PhACs) and endocrine-disrupting compounds (EDCs) can be bioaccumulated by aquatic organisms. However, the relative role of trophic transfers in the acquisition of emerging pollutants by aquatic organisms remains largely unexplored. In freshwater ecosystems, wastewater treatment plants are a major source of PhACs and EDCs. Here we studied the entrance of emerging pollutants and their flow through riverine food webs in an effluent-influenced river. To this end we assembled a data set on the composition and concentrations of a broad spectrum of PhACs (25 compounds) and EDCs (12 compounds) in water, biofilm, and three aquatic macroinvertebrate taxa with different trophic positions and feeding strategies (Ancylus fluviatilis, Hydropsyche sp., Phagocata vitta). We tested for similarities in pollutant levels among these compartments, and we compared observed bioaccumulation factors (BAFs) to those predicted by a previously-developed empirical model based on octanol–water distribution coefficients (Dow). Despite a high variation in composition and levels of emerging pollutants across food web compartments, observed BAFs in Hydropsyche and Phagocata matched, on average, those already predicted. Three compounds (the anti-inflammatory drug diclofenac, the lipid regulator gemfibrozil, and the flame retardant TBEP) were detected in water, biofilm and (at least) one macroinvertebrate taxa. TBEP was the only compound present in all taxa and showed magnification across trophic levels. This suggests that prey consumption may be, in some cases, a significant exposure route. This study advances the notion that both waterborne exposure and trophic interactions need to be taken into account when assessing the potential ecological risks of emerging pollutants in aquatic ecosystems.
Keywords: Bioaccumulation factors (BAFs); Biomagnification; Contaminants; Macroinvertebrates; Pharmaceutical drugs; dept.che

Diel Patterns of Pheromone Release by Male Sea Lamprey - Fissette, Skye D; Bussy, Ugo; Huerta, Belinda; Brant, Cory O; Li, Ke; Johnson, Nicholas S; Li, Weiming (Integrative and Comparative Biology, 2021)
Costs to producing sexual signals can create selective pressures on males to invest signaling effort in particular contexts. When the benefits of signaling vary consistently across time, males can optimize signal investment to specific temporal contexts using biological rhythms. Sea lamprey, Petromyzon marinus, have a semelparous life history, are primarily nocturnal, and rely on pheromone communication for reproduction; however, whether male investment in pheromone transport and release matches increases in spawning activity remains unknown. By measuring (1) 3keto-petromyzonol sulfate (3kPZS, a main pheromone component) and its biosynthetic precursor PZS in holding water and tissue samples at six points over the course of 24 hours and (2) 3kPZS release over the course of several days, we demonstrate that 3kPZS release exhibits a consistent diel pattern across several days with elevated pheromone release just prior to sunset and at night. Trends in hepatic concentrations and circulatory transport of PZS and 3kPZS were relatively consistent with patterns of 3kPZS release and suggest the possibility of direct upregulation in pheromone transport and release rather than observed release patterns being solely a byproduct of increased behavioral activity. Our results suggest males evolved a signaling strategy that synchronizes elevated pheromone release with nocturnal increases in sea lamprey behavior. This may be imperative to ensure that male signaling effort is not wasted in a species having a single, reproductive event.
Keywords: dept.che; peer-reviewed

Early life interactions with aquatic insects elicit physiological and behavioral stress responses in lake sturgeon (Acipenser fulvescens) - Wassink, Lydia; Riedy, Joseph J.; Huerta, Belinda; Johnson, Garrett; Larson, Douglas L.; Li, Weiming; Scribner, Kim T. (Environmental Biology of Fishes, 2021)
Predator encounters during early life can elicit behavioral and physiological responses that have fitness consequences during subsequent prey life stages. In threatened lake sturgeon (Acipenser fulvescens) and other lithophilic-spawning fishes, newly hatched larvae (free embryos) are exposed to abundant predators including aquatic insect larvae that co-occupy stream substrates. We investigated stress effects on lake sturgeon larvae after encounters with common aquatic insect predators by quantifying mortality, body size, cortisol levels, and swimming behavior. Free embryos were exposed to either Perlidae (stonefly obligate predators) or Isonychiidae (mayfly filterers and facultative predators) or to no predators (controls). Free embryos that encountered perlids experienced high mortality, elevated cortisol levels, and exhibited cortisol reactivity when subsequently exposed to an acute stressor. Free embryos that encountered isonychiids exhibited elevated mortality, and elevated cortisol and cortisol reactivity relative to controls. Findings indicate that lake sturgeon free embryos are stressed by exposure to members of benthic stream communities during early life stages (predation of nearby conspecifics), and that metrics of stress exhibited threat sensitivity. Data are consistent with predictions that individuals modulate antipredator behavior in response to the intensity of perceived predation threat in the environment. We determined that behavioral outcomes associated with encounters with aquatic insects altered future behavioral trajectories, potentially as an adaptive response that can affect predation rates in subsequent life stages. Results contribute to a broader understanding of how interspecies interactions among co-occurring predator and prey communities may impact individual fitness and fish population recruitment.
Keywords: Aquatic invertebrates; Behavioral plasticity; Early life mortality; Lake sturgeon; Threat sensitivity; dept.che; peer-reviewed

Fluvial biofilms exposed to desiccation and pharmaceutical pollution: New insights using metabolomics - Serra-Compte, Albert; Corcoll, Natàlia; Huerta, Belinda; Rodríguez-Mozaz, Sara; Sabater, Sergi; Barceló, Damià; Álvarez-Muñoz, Diana (Science of The Total Environment, 2018)
In many arid and semi-arid systems, biological communities in river ecosystems are submitted to flow interruption and desiccation, as well as to the impact of urban wastewaters. In this work, we studied (using a LC-LTQ-Orbitrap) the metabolomic response of biofilm communities exposed to both hydrological and chemical stressors. Fluvial biofilms were exposed to a mixture of 9 pharmaceuticals at a total concentration of 5000ng/L (mimicking concentrations and compounds found in polluted aquatic environments) and/or to seven days of desiccation, under laboratory conditions. The biosynthesis of fatty acids was the main metabolic pathway disrupted in biofilms. Endogenous biofilm's metabolites (metabolome) altered due to these stressors were identified. The metabolites that significantly changed only due to one of the stressors could be proposed as potential specific biomarkers. A biomarker of pharmaceutical exposure was the lysophosphatidic acid, which decreased a 160%, while for desiccation stearidonic acid (increased 160%), 16-Oxohexadecanoic acid (increased 340%) and palmitoleic acid (decreased 290%) were the biomarkers proposed. Besides, other metabolites showed different responses depending on the treatment, such as palmitic acid, linolenic acid, behenic acid, lignoceric acid and azelaic acid. The Carbon:Phosphorus (C:P) molar ratio increased due to all stress factors, whereas the algal community composition changed mainly due to desiccation. A possible relationship between those changes observed in structural parameters and the metabolome of biofilms was explored. Overall, our findings support the use of metabolomics to unravel at molecular level the effects from chemical and physical stressors on complex microbial communities, such as biofilms, and pinpoint biomarkers of exposure.
Keywords: Biofilms; Biomarkers; Environmental stressors; Metabolomic profiling; dept.che

Anti‐anxiety drugs and fish behavior: Establishing the link between internal concentrations of oxazepam and behavioral effects - Huerta, Belinda; Margiotta‐Casaluci, Luigi; Rodríguez‐Mozaz, Sara; Scholze, Martin; Winter, Matthew J.; Barceló, Damià; Sumpter, John P. (Environmental Toxicology and Chemistry, 2016)
Psychoactive drugs are frequently detected in the aquatic environment. The evolutionary conservation of the molecular targets of these drugs in fish suggests that they may elicit mode of action–mediated effects in fish as they do in humans, and the key open question is at what exposure concentrations these effects might occur. In the present study, the authors investigated the uptake and tissue distribution of the benzodiazepine oxazepam in the fathead minnow (Pimephales promelas) after 28 d of waterborne exposure to 0.8 μg L−1, 4.7 μg L−1, and 30.6 μg L−1. Successively, they explored the relationship between the internal concentrations of oxazepam and the effects on fish exploratory behavior quantified by performing 2 types of behavioral tests, the novel tank diving test and the shelter‐seeking test. The highest internal concentrations of oxazepam were found in brain, followed by plasma and liver, whereas muscle presented the lowest values. Average concentrations measured in the plasma of fish from the 3 exposure groups were, respectively, 8.7 ± 5.7 μg L−1, 30.3 ± 16.1 μg L−1, and 98.8 ± 72.9 μg L−1. Significant correlations between plasma and tissue concentrations of oxazepam were found in all 3 groups. Exposure of fish to 30.6 µg L−1 in water produced plasma concentrations within or just below the human therapeutic plasma concentration (HTPC) range in many individuals. Statistically significant behavioral effects in the novel tank diving test were observed in fish exposed to 4.7 μg L−1. In this group, plasma concentrations of oxazepam were approximately one‐third of the lowest HTPC value. No significant effects were observed in fish exposed to the lowest and highest concentrations. The significance of these results is discussed in the context of the species‐specific behavior of fathead minnow and existing knowledge of oxazepam pharmacology. Environ Toxicol Chem 2016;35:2782–2790. © 2016 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.
Keywords: dept.che

Spatiotemporal Patterns in Profiles of Amino Acids Indicates They Are Unlikely Singular Olfactory Cues Underlying Natal Homing in Migratory Fishes - Kimmel, Jacob; Buchinger, Tyler; Tamrakar, Sonam; Huerta, Belinda; Larson, Douglas; Baker, Edward; Zorn, Troy; Scribner, Kim; Li, Weiming (Freshwater Biology, 2025)
ABSTRACT Migratory fishes are renowned for their ability to home to natal streams for spawning. Learned olfactory cues play a critical role in natal homing of Pacific salmon and other fishes, but the underlying chemical signature of streams remains poorly understood after decades of study. The molecules that convey a stream‐specific odour must differ among sites but remain constant over time. Among leading odorant candidates are amino acids; however, little research has assessed the spatial and temporal variability of amino acid profiles in streams. We report a comprehensive chemical study of dissolved amino acids as potential olfactory cues for homing by migratory fish. Specifically, we profiled amino acids in water from 23 streams in the upper Laurentian Great Lakes basin over 2 years. We investigated variation in amino acid profiles (1) among regions and rivers within a year, (2) between years and (3) among sites and across the seasons of migration and early life history within a stream. Liquid‐chromatography tandem mass spectrometry revealed nanomolar concentrations for most of the 20 L‐amino acids measured, above the levels detectable by studied migratory fishes. Moreover, amino acid profiles were temporally stable between 2 years and across an annual season from adult spawning migration through offspring early‐life development within a stream. However, spatial differences in amino acid profiles were evident primarily over large geographic distances (among regions) but not among tributaries within regions or among sites within a stream. Collectively, our results indicate dissolved amino acids may be consistent components of rivers' odorant profiles but suggest additional molecules are likely important for natal homing of migratory fishes to specific spawning sites. We suggest that future studies consider the combined importance of amino acids and molecules from other chemical classes. Understanding the chemical basis of olfactory‐guided natal homing is especially important as human activities could alter the odorant profiles of streams and thereby disrupt fish migrations and negatively impact population recruitment.
Keywords: Biology; Ecology; Evolutionary biology; Great Lakes; Homing (biology); Neuroscience; Olfaction; Olfactory cues; Olfactory system; Zoology; dept.che; navigation; olfactory imprinting; peer-reviewed; site fidelity; sturgeon

Uptake and Metabolism of Human Pharmaceuticals by Fish: A Case Study with the Opioid Analgesic Tramadol - Tanoue, Rumi; Margiotta-Casaluci, Luigi; Huerta, Belinda; Runnalls, Tamsin J.; Nomiyama, Kei; Kunisue, Tatsuya; Tanabe, Shinsuke; Sumpter, John P. (Environmental Science & Technology, 2017)
Recent species-extrapolation approaches to the prediction of the potential effects of pharmaceuticals present in the environment on wild fish are based on the assumption that pharmacokinetics and metabolism in humans and fish are comparable. To test this hypothesis, we exposed fathead minnows to the opiate pro-drug tramadol and examined uptake from the water into the blood and brain and the metabolism of the drug into its main metabolites. We found that plasma concentrations could be predicted reasonably accurately based on the lipophilicity of the drug once the pH of the water was taken into account. The concentrations of the drug and its main metabolites were higher in the brain than in the plasma, and the observed brain and plasma concentration ratios were within the range of values reported in mammalian species. This fish species was able to metabolize the pro-drug tramadol into the highly active metabolite O-desmethyl tramadol and the inactive metabolite N-desmethyl tramadol in a similar manner to that of mammals. However, we found that concentration ratios of O-desmethyl tramadol to tramadol were lower in the fish than values in most humans administered the drug. Our pharmacokinetic data of tramadol in fish help bridge the gap between widely available mammalian pharmacological data and potential effects on aquatic organisms and highlight the importance of understanding drug uptake and metabolism in fish to enable the full implementation of predictive toxicology approaches.
Keywords: dept.che

Internal exposure dynamics drive the Adverse Outcome Pathways of synthetic glucocorticoids in fish - Margiotta-Casaluci, Luigi; Owen, Stewart F.; Huerta, Belinda; Rodríguez-Mozaz, Sara; Kugathas, Subramanian; Barceló, Damià; Rand-Weaver, Mariann; Sumpter, John P. (Scientific Reports, 2016)
The Adverse Outcome Pathway (AOP) framework represents a valuable conceptual tool to systematically integrate existing toxicological knowledge from a mechanistic perspective to facilitate predictions of chemical-induced effects across species. However, its application for decision-making requires the transition from qualitative to quantitative AOP (qAOP). Here we used a fish model and the synthetic glucocorticoid beclomethasone dipropionate (BDP) to investigate the role of chemical-specific properties, pharmacokinetics, and internal exposure dynamics in the development of qAOPs. We generated a qAOP network based on drug plasma concentrations and focused on immunodepression, skin androgenisation, disruption of gluconeogenesis and reproductive performance. We showed that internal exposure dynamics and chemical-specific properties influence the development of qAOPs and their predictive power. Comparing the effects of two different glucocorticoids, we highlight how relatively similar in vitro hazard-based indicators can lead to different in vivo risk. This discrepancy can be predicted by their different uptake potential, pharmacokinetic (PK) and pharmacodynamic (PD) profiles. We recommend that the development phase of qAOPs should include the application of species-specific uptake and physiologically-based PK/PD models. This integration will significantly enhance the predictive power, enabling a more accurate assessment of the risk and the reliable transferability of qAOPs across chemicals.
Keywords: Ecophysiology; Environmental sciences; Physiology; dept.che

Effects of flow intermittency and pharmaceutical exposure on the structure and metabolism of stream biofilms - Corcoll, Natàlia; Casellas, Maria; Huerta, Belinda; Guasch, Helena; Acuña, Vicenç; Rodríguez-Mozaz, Sara; Serra-Compte, Albert; Barceló, Damià; Sabater, Sergi (Science of The Total Environment, 2015)
Increasing concentrations of pharmaceutical compounds occur in many rivers, but their environmental risk remains poorly studied in stream biofilms. Flow intermittency shapes the structure and functions of ecosystems, and may enhance their sensitivity to toxicants. This study evaluates the effects of a long-term exposure of biofilm communities to a mixture of pharmaceutical compounds at environmental concentrations on biofilm bioaccumulation capacity, the structure and metabolic processes of algae and bacteria communities, and how their potential effects were enhanced or not by the occurrence of flow intermittency. To assess the interaction between those two stressors, an experiment with artificial streams was performed. Stream biofilms were exposed to a mixture of pharmaceuticals, as well as to a short period of flow intermittency. Results indicate that biofilms were negatively affected by pharmaceuticals. The algal biomass and taxa richness decreased and unicellular green algae relatively increased. The structure of the bacterial (based on denaturing gradient gel electrophoresis of amplified 16S rRNA genes) changed and showed a reduction of the operational taxonomic units (OTUs) richness. Exposed biofilms showed higher rates of metabolic processes, such as primary production and community respiration, attributed to pharmaceuticals stimulated an increase of green algae and heterotrophs, respectively. Flow intermittency modulated the effects of chemicals on natural communities. The algal community became more sensitive to short-term exposure of pharmaceuticals (lower EC50 value) when exposed to water intermittency, indicating cumulative effects between the two assessed stressors. In contrast to algae, the bacterial community became less sensitive to short-term exposure of pharmaceuticals (higher EC50) when exposed to water intermittency, indicating co-tolerance phenomena. According to the observed effects, the environmental risk of pharmaceuticals in nature is high, but different depending on the flow regime, as well as the target organisms (autotrophs vs heterotrophs).
Keywords: Algae; Bacteria; Ecotoxicology; Intermittent rivers; Multiple stressors; Pollution; dept.che

Monitoring of emerging contaminants of concern in the aquatic environment: a review of studies showing the application of effect-based measures - Yusuf, Azeez; O'Flynn, Dylan; White, Blanaid; Holland, Linda; Parle-McDermott, Anne; Lawler, Jenny; McCloughlin, Thomas; Harold, Denise; Huerta, Belinda; Regan, Fiona (Analytical Methods, 2021)
Water scarcity is increasingly a global cause of concern mainly due to widespread changes in climate conditions and increased consumptive water use driven by the exponential increase in population growth. In addition, increased pollution of fresh water sources due to rising production and consumption of pharmaceuticals and organic chemicals will further exacerbate this concern. Although surface water contamination by individual chemicals is often at very low concentration, pharmaceuticals for instance are designed to be efficacious at low concentrations, creating genuine concern for their presence in freshwater sources. Furthermore, the additive impact of multiple compounds may result in toxic or other biological effects that otherwise will not be induced by individual chemicals. Globally, different legislative frameworks have led to pre-emptive efforts which aim to ensure good water ecological status. Reports detailing the use and types of effect-based measures covering specific bioassay batteries that can identify specific mode of actions of chemical pollutants in the aquatic ecosystem to evaluate the real threat of pollutants to aquatic lives and ultimately human lives have recently emerged from monitoring networks such as the NORMAN network. In this review, we critically evaluate some studies within the last decade that have implemented effect-based monitoring of pharmaceuticals and organic chemicals in aquatic fauna, evaluating the occurrence of different chemical pollutants and the impact of these pollutants on aquatic fauna with special focus on pollutants that are contaminants of emerging concern (CEC) in urban wastewater. A critical discussion on studies that have used effect-based measures to assess biological impact of pharmaceutical/organic compound in the aquatic ecosystem and the endpoints measurements employed is presented. The application of effect-based monitoring of chemicals other than assessment of water quality status is also discussed.
Keywords: dept.che; peer-reviewed

Behavioral Responses of Sea Lamprey to Varying Application Rates of a Synthesized Pheromone in Diverse Trapping Scenarios - Johnson, Nicholas S.; Lewandoski, Sean A.; Alger, Bethany J.; O’Connor, Lisa; Bravener, Gale; Hrodey, Peter; Huerta, Belinda; Barber, Jessica; Li, Weiming; Wagner, C. Michael; Siefkes, Michael J. (Journal of Chemical Ecology, 2020)
Use of the first fish pheromone biopesticide, 3-keto petromyzonol sulfate (3kPZS) in sea lamprey (Petromyzon marinus) control requires an understanding of both how the amount 3kPZS applied to a trap relates to catch, and how that relationship varies among stream types. By conducting 3kPZS dose-response experiments over two years and across six varied trapping contexts, we conclude (1) that 3kPZS application is best standardized by how much is emitted from the trap instead of the fully mixed concentration achieved downstream, and (2) that 3kPZS is more effective in wide streams (>30 m). In wide streams, emission of 3kPZS at 50 mg hr.−1 from the trap increased capture rate by 10–15% as sea lamprey were 25–50% more likely to enter the trap after encounter. However, in narrow streams (< 15 m), 50 mg hr.−1 3kPZS generally reduced probabilities of upstream movement, trap encounter, and entrance. While 3kPZS significantly influenced upstream movement, encounter, and capture probabilities, these behaviors were also highly influenced by water temperature, stream width, sea lamprey length, and sex. This study highlights that a pheromone component in a stream environment does not ubiquitously increase trap catch in all contexts, but that where, how, and when the pheromone is applied has major impacts on whether it benefits or hinders trapping efforts.
Keywords: Application rate; Invasive species; Lamprey; Pheromone; Trap; dept.che; peer-reviewed